Clinical ophthalmology : a systematic approach - Kanski, Jack J.; Bowling, Brad (Edinburgh ; New York : Elsevier, 2011)
An ophthalmic resource that offers readers with online materials including full text, downloadable images and self-assessment tools. A trusted reference through seven editions for thousands of students and practitioners. Established as one of the world's leading ophthalmic resources, it has now been updated for a new generation of readers with many new features including self-assessment tools.
Includes index.
oif 14/05/14
Loan
Keywords: Ophthalmology; Eye Diseases